1998
DOI: 10.2307/3237281
|View full text |Cite
|
Sign up to set email alerts
|

Flood drift and propagule bank of aquatic macrophytes in a riverine wetland

Abstract: Abstract. Drift of aquatic macrophyte propagules was investigated in a wetland along the River Rhône, during the first flood after the growing season (i.e. in the winter of 1995–1996). Input and output drift were studied at the beginning, around the top, and at the end of the river overflow in the upper reach of a cut‐off channel. The soil propagule bank was sampled along the study area before and after the flood. The amount and composition of viable propagule drift and bank were determined, analysed and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 42 publications
1
63
3
1
Order By: Relevance
“…First, high numbers of vegetative propagules are dispersed by hydrochory, especially during the winter months. In rivers, Cellot et al (1998) found that the number of vegetative propagules in the water increased by flooding as greater turbulence caused more fragmentation of aquatic and riparian plants. In the ponds of this study, the increased number of vegetative propagules in autumn and winter can most likely be explained by natural decay of (submerged) macrophytes and the increased turbulence in the water by stronger winds as they were not dredged.…”
Section: Discussionmentioning
confidence: 99%
“…First, high numbers of vegetative propagules are dispersed by hydrochory, especially during the winter months. In rivers, Cellot et al (1998) found that the number of vegetative propagules in the water increased by flooding as greater turbulence caused more fragmentation of aquatic and riparian plants. In the ponds of this study, the increased number of vegetative propagules in autumn and winter can most likely be explained by natural decay of (submerged) macrophytes and the increased turbulence in the water by stronger winds as they were not dredged.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative organs, such as floating turions or the shoot fragments of some aquatic plants and tideland halophytes, are known to be able to contribute as colonizers (Grace 1993;Sanchez et al 2001;Capers 2003). Even rhizomes and subterranean tubers of riparian species can be dispersed, particularly in the case of floods (Cellot et al 1998;Khudamrongsawat et al 2004;Decruyenaere & Holt 2005;Minchinton 2006). However, we have never seen floating plant parts of C. rugulosa at our study site, whereas drifting reed fragments, Phragmites australis, are fairly common in the Ohashi River estuary (S. Araki & H. Kunii, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Increased depth would promote flood-tolerant species higher on the elevation gradient, and increased duration would promote clonal growth and the production and dispersal of propagules by flood-tolerant and aquatic plants (cf. Cellot et al, 1998). This will increase the time available for plants like E. acuta to spread via clonal growth.…”
Section: Future Trialsmentioning
confidence: 99%